Partial molar pregnancy with live fetus in first trimester: what should we do next - Eric Edwin; Uki Retno Budihastuti; Cut Sheira Elnita (Jurnal Kedokteran Syiah Kuala, 2020)
Abstract. The incidence of a normal live fetus with a partial mole is extremely rare, and it varies between 5 per 100000 and 1 per 10000 of the pregnancies. A partial molar pregnancy is a variation of a molar pregnancy in which an embryo either develops incompletely or with multiple structural anomalies.A 27-year-old Primigravide at 13 weeks of gestation got admitted with spotting per vaginam, excessive nausea and vomiting, and her ultrasound revealed a hydropic placenta with multiple cysts with a live fetus. Regarding these findings, the patient continued her pregnancy under close observation, and advanced sonographic evaluations were done to rule out other differentials. Ultrasonography found mosaicism in the partial mole (mostly diploid, a small part is triploid). In this condition, the prognosis condition for the fetus to be born safely is still probable. Ethics committee meetings are held with the consideration of the fetus's condition, whether monitoring is carried out regularly, and terminating the pregnancy in case of fetal emergency.The optimal management of hydatidiform mole with the coexistent live fetus is currently uncertain. Antenatal consultation should include a detailed discussion of maternal and fetal risks. It is also necessary to have close follow-up and evaluation of the patient's condition during the antenatal and postnatal period. Keywords: first trimester, live fetus , management, partial molar pregnancy